Comparative Study on Flexural Performance of Foamed Concrete Beam Containing Plastic Fibres - Ali Keerio, Manthar; Lakhiar, Muhammad Tahir; Sohu, Samiullah (International Journal of Sustainable Construction Engineering and Technology, 2019)
Foamed concrete is considered as light weight concrete which possesses lot of benefits in context of speedy construction, light weight and durability. In this study, foamed concrete beam, containing the plastic fibers were analyzed under flexural load by experimentally and also by finite element analysis in terms of load bearing capacity, load deflection profile and cracking pattern. The Finite element analysis (FEA) was conducted by utilizing ABAQUS software to simulate the foamed concrete beam under flexure load. The beam consist the dimension was 100mm thickness, 200mm breadth, 1000 mm length. The experimental and FEA outcomes were compared in context of the beam’s ultimate load, load deflection and cracking pattern. The outcomes demonstrate that the difference between ultimate loads was 5 to 8% between FEA and experimental results whereas the maximum deflection was 3 to 7 % decreased in FEA compare to the experimental analysis. The parametric was conducted by changing the reinforcement area the results demonstrates that by increasing the main reinforcement area the ultimate load was rises and deflection was decreases compare to the control sample. To approve a single suggestion, mouse over it and click "✔" Click the bubble to approve all of its suggestions. To approve a single suggestion, mouse over it and click "✔" Click the bubble to approve all of its suggestions. To approve a single suggestion, mouse over it and click "✔" Click the bubble to approve all of its suggestions. To approve a single suggestion, mouse over it and click "✔" Click the bubble to approve all of its suggestions. To approve a single suggestion, mouse over it and click "✔" Click the bubble to approve all of its suggestions. To approve a single suggestion, mouse over it and click "✔" Click the bubble to approve all of its suggestions.